Immunogenicity and Protective Efficacy of a Novel Recombinant BCG Strain Overexpressing Antigens Ag85A and Ag85B. (18th April 2012) - Wang, Chun; Fu, Ruiling; Chen, Zhenhua; Tan, Kun; Chen, Lingxia; Teng, Xindong; Lu, Jia; Shi, Chunwei; Fan, Xionglin
Abstract : Recombinant Bacillus Calmette-Guérin (rBCG) strain is the promising vaccine candidate for tuberculosis (TB) prevention, which aims at providing more enduring and enhanced protection than the parental BCG vaccine. In this study, three rBCG strains overexpressing immunodominant antigens Ag85B (rBCG::85B), Ag85A (rBCG::85A), or both (rBCG::AB) of Mycobacterium tuberculosis were constructed, respectively. rBCG strains showed higher level of overexpression of Ag85A and/or Ag85B proteins than BCG containing empty vector pMV261(rBCG::261), which had low levels of endogenous expression of both proteins as expected. rBCG::AB strain could provide the strongest short-term and long-term protection in the lung against intravenous infection with virulent M. tuberculosis than rBCG::261 control and other two rBCG strains overexpressing single antigen. The stronger and longer-lasting protection provided by rBCG::AB than rBCG::261 was correlated with systemic in vitro antigen-specific IFN- γ responses. Therefore, our results indicate that rBCG::AB could be a very promising TB vaccine candidate and should be further evaluated for the preclinical test.